Морфологічні дослідження плодів у межах роду Anemone L. (Ranunculaceae Juss.) для таксономії - Ziman, S.M.; Tsarenko, O.M.; Bulakh, O.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
Results of comparative-morphological study of the genus Anemone L. are given. According to the modern data, this genus includes 16 subgenera, 19 sections, 5 subsections, 27 series and 118 species. We argumented the use in the taxonomy of Anemone ca. 25 carpologic characters (against 10 characters which were used earlier). In addition to fruits shape (ovoid, ellipsoid, globose, compressed, ribbed or winged), the peculiarities of their basal and apical parts (sessile or not, narrowed or dilated). The peculiarities of shape and size of stylodia and stigmas were clarificated.